Using ground data from the Global Terrestrial Network of Permafrost (GTN-P) for the Evaluation of the ESA DUE Permafrost remote sensing derived Products Land Surface Temperature and ASCAT Surface State Flag - Elger, Kirsten; Heim, Birgit; Bartsch, Annett; Paulik, Christoph; Duguay, Claude; Hachem, Sonia; Soliman, Aiman; Lantuit, Hugues; Boike, Julia; Seifert, Frank Martin (The Northern Publisher (Severnoye Izdatelstvo), 2012)
The ESA Data User Element (DUE) Permafrost project provides a mid-to-long-term Earth observation service for permafrost remote sensing derived applications for Northern high-latitudinal permafrost areas. The DUE Permafrost remote sensing products are land surface temperature, surface soil moisture, frozen/thawed surface status, elevation, land cover and surface waters. A major component is the evaluation of the DUE Permafrost products to test their scientific validity for high-latitude permafrost landscapes. These case studies evaluate two DUE Permafrost products (MODIS Land Surface Temperature and ASCAT Surface State Flag) by comparing the results with field-based data obtained by the Global Terrestrial Network of Permafrost (GTN-P). First results showed good correlation which suggests that the DUE Permafrost approach is a promising one for long-term monitoring of permafrost surface conditions. Furthermore it demonstrates the great benefit of freely available ground truth databases for the evaluation of remote sensing derived products.